2017
DOI: 10.1108/ijoa-09-2016-1068
|View full text |Cite
|
Sign up to set email alerts
|

Relations at workplace, cynicism and intention to leave

Abstract: Purpose Although employee relations are recognised as important mechanisms for initiating organisational competitiveness and output, existing research has focused primarily on how these relations embed employees’ job and performance, rather than on the declining outcomes from such relations. This paper aims to integrate research on co-worker relations at workplace and cynicism with social exchange as a theoretical grounding to propose a process model that focuses on how employees’ positive relationship at work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 86 publications
(84 reference statements)
0
20
0
1
Order By: Relevance
“…Generally, ER are considered to be the main responsibility of HRM functions within organizations (Blyton, Turnbull 1998). ER are recognized as a factor in shaping employee satisfaction and intention to stay (Abugre 2017). The notion of ER refers to the positive relationship between two or more individuals involved in a mutual relationship within the social and authority dimensions within an organizational context (Asghar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ER are considered to be the main responsibility of HRM functions within organizations (Blyton, Turnbull 1998). ER are recognized as a factor in shaping employee satisfaction and intention to stay (Abugre 2017). The notion of ER refers to the positive relationship between two or more individuals involved in a mutual relationship within the social and authority dimensions within an organizational context (Asghar et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by existing studies of Cartwright and Holmes (2006), who documented that employers can reduce cynicism among their employees by increasing EE. Similarly, Abugre (2017) found that employees' satisfaction can be increased through effective interpersonal interactions and engagement that will help in reducing OC at workplace. It was also evident from previous studies that EE matters within an organisation, on the one hand, and that disengaged employees, on the other hand, increased costs for an organisation due to high absenteeism (Mousa, 2017a), lower productivity and high turnover of staff (Saari and Judge, 2004;Truss et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The concept of leadership is described by Xirasagar (2008) where transformational leadership styles include: idealized influence, inspirational motivation, intellectual simulation, individual consideration. Transformational leadership will make subordinates are given authority and are encouraged to creatively and innovatively question their beliefs, assumptions, values, and change attitudes when needed, as well as the courage to take risks when needed (Abugre, 2017;Gupta & Shaheen, 2017;Gupta, Singh, & Bhattacharya, 2017), without being judged when making mistakes (Griffioen, Doppenberg, & Oostdam, 2017;Khasawneh, Omari, & Abu-Tineh, 2012). This finding is reinforced in a previous study by (Bai, Lin, & Li, 2016) which stated that, transformational leadership created a dynamic organizational vision to create an innovation.…”
Section: Literature Reviewmentioning
confidence: 90%